Sustainability criteria for the production of biofuels and bioliquids for energy applications. Principles, criteria, indicators and verifiers. Calculation methods of the greenhouse gas emission balance using a life cycle analysis approach Part 4, (19th November 2019) - British Standards Institution,
No abstract available